Anxiety level of third trimester pregnant women towards antenatal care visit compliance during the COVID-19 pandemic - Yetti Fidianingsih; Nanik Setiyawati; Yuliantisari Retnaningsih (Jurnal Kesehatan Ibu dan Anak, 2022)
The COVID-19 pandemic has impacted all areas of life, one of those is pregnant women. During the COVID-19 pandemic, pregnant women are terrified to conduct a pregnancy check. The purpose of this study was to identify the correlation between the anxiety level of third trimester pregnant women towards antenatal care (ANC) visits during the Covid-19 pandemic. The study used a cross sectional study at the Sanden Public Health Center (PHC) from January to March 2022. The sample was taken using purposive sampling of 45 people. Data was collected by using a questionnaire. Data analysis used univariate and bivariate (chi square) analysis.The results of the univariate analysis showed that the majority of pregnant women who did not fulfill the visit compliance experienced severe anxiety, namely 7 people (87.5%). While the majority of pregnant women who met the compliance visit experienced mild anxiety, namely 24 people (85.7%). The results of the bivariate analysis showed that there was a relationship between the level of anxiety of pregnant women in the third trimester and the level of compliance with ANC visits during the COVID-19 pandemic at the Sanden PHC in 2021 with a p value of 0.000. The majority of respondents at the Sanden PHC, Bantul Regency, were classified as not at risk, not working, highly educated, multigravida, experiencing mild anxiety levels, and fulfilling ANC visits. There is a relationship between the level of anxiety of pregnant women in the third trimester and the level of compliance with ANC visits during the COVID-19 pandemic.